Working from the ground up: Prosperity for farmers in Soroti District starts in the soil. Issue 2 (28th June 2022) - Barron, Christopher
Abstract: Agriculture in much of Uganda is struggling, especially in Soroti District. Many of the issues are linked to the poor soils that are present in this region. Farmers in Soroti District will need to adopt various soil conservation techniques and practices to improve their soils over time and increase production. Core Ideas: There are significant issues with agriculture in Uganda. In Soroti District, many of these issues are linked to poor soils. Farmers will need to take special steps in order to improve these soils and make them productive.